Design of high power piezoelectric ceramic digital drive power based on FPGA - Kang Yukuang; Zheng Hanlin; Huang Qiao; Shen Wei (Dianzi Jishu Yingyong)
At present, the stacked piezoelectric ceramics can generate a thrust of up to 70 kN, and have nanometer-level precision positioning. In order to improve the output performance and accuracy of piezoelectric ceramic drive power, a design of high-power and high-precision piezoelectric ceramic digital drive power based on FPGA is proposed, which has a fixed output gain of 100 times. The driving power supply uses FPGA as the control core, adopts a half-bridge inverter circuit topology, and introduces closed-loop control to adjust the output voltage. Under a piezoelectric ceramic load with an equivalent capacitance of 5 μF, the input bandwidth of the drive power supply is 10 Hz~800 Hz, the output power can reach 1 kW, the voltage ripple is less than 30 mV, and the output accuracy is as high as 99.3%. The experimental results show that the driving power supply can be used in the application fields of stacked piezoelectric ceramics such as vibrating table and hexapod control platform, and has good driving performance.